Simple Workflow and Comparison of Media for hPSC‐Cardiomyocyte Cryopreservation and Recovery. (21st September 2020) - Miller, Duncan C.; Genehr, Carolin; Telugu, Narasimha S.; Kurths, Silke; Diecke, Sebastian
Abstract: Great progress has been made with protocols for the differentiation and functional application of hPSC‐cardiomyocytes (hPSC‐CMs) in recent years; however, the cryopreservation and recovery of hPSC‐CMs still presents challenges and few reports describe in detail the protocols and general workflow. In order to facilitate cryopreservation and recovery of hPSC‐CMs for a wide range of applications, we provide detailed information and step‐by‐step protocols. The protocols are simple and use common reagents. They are comprised of a fast dissociation, cryopreservation using standard equipment, and gentle recovery following thawing. We discuss various features of the protocols, as well as their utilization in the context of common hPSC‐CM differentiation and application workflows. Finally, we compare two proprietary and two common in‐house formulations of cryopreservation media used for hPSC‐CMs, and despite differences in their price and composition find broadly similar recovery rates and cellular function after thawing. © 2019 The Authors. Basic Protocol 1 : Dissociation and cryopreservation of hPSC‐CMs Basic Protocol 2 : Thawing and recovery of cryogenically frozen hPSC‐CMs